Modification of distance factor in rain attenuation prediction for short-range millimeter-wave links - Ali Hussein Budalal, Asma; Islam, Md Rafiqul; Abdullah, Khaizuran; Abdul Rahman, Tharek (IEEE, 2020)
Prediction accuracy of rain attenuation on shortrange millimeter-wave (mm-wave) terrestrial links is of the utmost importance for signal strength prediction and link budget of 5G systems and beyond. This letter contributes to the prediction of rain attenuation over millimeter-wave frequencies for a short-range path (less than 1 km). Interestingly, rain-induced attenuation predicted by utilizing ITU-R P.530-17 largely overestimates the measured data at 26 and 38 GHz with 300 m path length in Malaysia. This is due to the inclusion of the distance factor, which ranges between 2.5 (f = 38 GHz) and 2.54 (26 GHz). The behavior of the distance factor is investigated thoroughly, and it is found that the maximum values of the distance factor are inconsistent for the path lengths less than 1 km. Consequently, a modification for the distance factor r in ITU-R P530.17 has been proposed. The rain attenuation data measured are utilized to validate and improve the proposed modifications. In addition, available rain attenuation measurements at 25 GHz for 223 m path length in Japan and 75 GHz for 10 m path length in Korea are also utilized for validation. Subsequently, several available measurements from different locations are used to validate the accuracy of the proposed model and are found in good agreement